Asadova, Mahabbat - (:unkn) unknown (My University, 2026)
Mahabbat Asadova, PhD in Philology, Associate Professor, graduated from the Azerbaijan Pedagogical Institute of Foreign Languages in 1987 with a degree in English and French Language Teaching. She worked as an English teacher in secondary schools from 1987 to 1995 before joining the Azerbaijan University of Architecture and Construction (AzUAC) in 1995. She has served as an Associate Professor at the Department of Foreign Languages since 2010. She completed postgraduate studies in Language Theory at the Institute of Linguistics named after Nasimi of the Azerbaijan National Academy of Sciences and earned her PhD in Philology in 2004 with a dissertation on object clauses in English and Azerbaijani. She was awarded the academic title of Associate Professor in 2012. Her research interests include English and Azerbaijani comparative linguistics, syntax, language theory, and English language teaching.